Current Opportunities and Challenges in Biopolymer Thin Film Analysis—Determination of Film Thickness - Spirk, Stefan; Palasingh, Chonnipa; Nypelö, Tiina (Frontiers in Chemical Engineering, 2021)
Polymer thin films with thickness below 100 nm are a fascinating class of 2D materials with commercial and research applications in many branches ranging from coatings to photoresists and insulating materials, to mention just a few uses. Biopolymers have extended the scope of polymer thin films with unique materials such as cellulose, cellulose nanocrystals, cellulose nanofibrils with tunable water uptake, crystallinity and optical properties. The key information needed in thin biopolymer film use and research is film thickness. It is often challenging to determine precisely and hence several techniques and their combinations are used. Additional challenges with hydrophilic biopolymers such as cellulose are the presence of humidity and the soft and often heterogenous structure of the films. This minireview summarizes currently used methods and techniques for biopolymer thin film thickness analysis and outlines challenges for accurate and reproducible characterization. Cellulose is chosen as the representative biopolymer.